2000
DOI: 10.1103/physrevb.61.14327
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical behavior of the random-bond transverse Ising model with four-spin interactions

Abstract: We study the time evolution of the one-dimensional random-bond transverse Ising model with four-spin interactions. We calculate the time-dependent correlation function as well as the longitudinal rclaxation 'function of the infinite chain. We analyze how the presence of disordeT affect the dynamical behavior of the~ system in comparison with the pure model. We find that the main effect of disorder is to produce a crossover from a central mode to a collective-mode type of dynamics, as the concentration of weake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…[4][5][6][7] Recently, some results for the dynamics of the 1-D disordered quantum spin models are reported. [8][9][10][11][12] One simple yet important example of the disordered quantum spin chains is the 1-D random transverse Ising model ͑RTIM͒, where both the exchange couplings J i and the transverse fields B i are considered as random variables. This model has a well-known physical interpretation in connection not only with some quasi-one-dimensional hydrogenbonded ferroelectric crystals like Cs͑H 1−x D x ͒ 2 PO 4 , PbH 1−x D x PO 4 , etc., 13,14 but also with Ising spin glass such as LiHo 0.167 Y 0.833 F 4 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Recently, some results for the dynamics of the 1-D disordered quantum spin models are reported. [8][9][10][11][12] One simple yet important example of the disordered quantum spin chains is the 1-D random transverse Ising model ͑RTIM͒, where both the exchange couplings J i and the transverse fields B i are considered as random variables. This model has a well-known physical interpretation in connection not only with some quasi-one-dimensional hydrogenbonded ferroelectric crystals like Cs͑H 1−x D x ͒ 2 PO 4 , PbH 1−x D x PO 4 , etc., 13,14 but also with Ising spin glass such as LiHo 0.167 Y 0.833 F 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The three spin-interactions in the spin chain can induce the quantum criticality that cannot be measured by concurrence, because three-spin interactions generate three-qubit entanglement [28,29] . Four-body interactions play important roles in phase transitions in condensed matters [21][22][23][24][25][26][27] , and relate to four-body entanglement, which is still an open problem currently. Simulation of quantum system is one of the main applications of future quantum computers.…”
mentioning
confidence: 99%
“…For example, the three-spin interactions can speed up the quantum state transfer in the Heisenberg spin chain [20] . Four-body interactions have attracted much interest recently [21][22][23][24][25][26][27] . The systems with manybody interactions can exhibit interesting phase transition behaviors [21][22][23][24][25][26][27][28][29] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have investigated the effects of Gaussian disorder on the dynamics of the 1-D RTIM [12], and have found that there are two crossovers when the standard deviation of random variables is small and there is no crossover if the value of the standard deviation is large enough. Besides, the dynamical behavior of the random-bond transverse Ising model with four-spin interactions [13] and the disordered XY chain [9,10,11] have been studied.…”
Section: Introductionmentioning
confidence: 99%